Ameliorating effects of ethanol extract of root bark of Salacia nitida on blood electrolyte and renal perturbations in Plasmodium berghei-infected mice - Barine Innocent Nwiloh; Augustine Amadikwa Uwakwe (Universidade de São Paulo, 2023)
Abstract Malaria, a disease of public health concern is a known cause of kidney failure, and dependence on herbal medicines for its treatment is increasing due to the high cost of drugs. So this study is designed to evaluate the ameliorating effect of ethanol extract from Salacia nitida root bark on electrolyte and renal perturbations in Plasmodium berghei-infected mice. Thirty malariainfected mice divided into five groups of six mice each and another group of six uninfected mice were used for the study. 280, 430, and 580 mg/kg of extract were given to infected mice in groups B, C, and D, 4 mg/kg of artesunate given to group E mice, and 4 ml/kg of physiological saline given to group A and uninfected group F mice for five days. Serum Na+, K+, HCO3, Cl-, TB, urea, creatinine, BUN concentrations, and BUN/creatinine ratio were determined using standard methods. Results showed significant increases (p < 0.05) in Na+, K+, and HCO3 and decreases in Cl-, TB, urea, creatinine, BUN, and BUN/creatinine ratio in the infected treated mice in groups B - E. This study showed that ethanol extract of S. nitida root bark is efficient in the treatment of renal disorders and blood electrolyte perturbations.